1969
DOI: 10.1901/jeab.1969.12-539
|View full text |Cite
|
Sign up to set email alerts
|

SELECTIVE ATTENTION: THE EFFECTS OF COMBINING STIMULI WHICH CONTROL INCOMPATIBLE BEHAVIOR1

Abstract: Four rhesus monkeys learned both a color and tilt discrimination. The stimuli were combined to produce incompatible behavior. The behavior controlled by one set of stimuli was reinforced until “errors” virtually disappeared. The stimuli were tested separately again. Sixteen replications of the entire procedure indicated that the stimuli producing “errors” were ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
1
21

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 15 publications
3
56
1
21
Order By: Relevance
“…If both of these controlling relations are presumed to be functional , then what makes a subject more likely to select one than the other? The problem may be one of selective attention (e.g., Born, Snow, & Herbert, 1969;Ray, 1969;Reynolds, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…If both of these controlling relations are presumed to be functional , then what makes a subject more likely to select one than the other? The problem may be one of selective attention (e.g., Born, Snow, & Herbert, 1969;Ray, 1969;Reynolds, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…Discriminative baselines were shown to involve mixtures of different stimulus-response relations (Sidman, 1969). And controlling stimulus-response relations were shown to have the properties ofoperant responses more generally (Ray, 1969). "Stimulus control topography" was chosen to help communicate these and other aspects of the subject matter.…”
Section: Stimulus Control Topographymentioning
confidence: 99%
“…Whereas response shaping refers to gradual changes in the response requirements of a reinforcement contingency, stimulus shaping would refer to gradual changes in the stimulus control requirements. Consistent with this usage, Ray (1969) sought to introduce the term "stimulus control topography" into the language of behavior analysis. The term was intended to parallel "response topography."…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Responses to such configurations are necessarily forced choice and we say that one relation controlled on that particular trial even though both relations are potentially functional. Where it has been demonstrated that more than one relation exists, and selection of one or the other comparison occurs, the construct of selective attention is invoked (Ray, 1969), which describes, but does not explain, the resulting stimulus control where there is more than one possible controlling relation. In the natural environment, it seems reasonable to consider the existence of matching-to-sample configurations that consist of more than one functional stimulus relation, only one of which can be functional on an occasion because the subject can only make one response.…”
Section: Experimental Analysis Ofhuman Behavior and These Studiesmentioning
confidence: 99%